Integrative analysis of fungal communities in three types of Baijiu Daqu using third-generation sequencing and culturomics - Wei, Yu-Hua; Han, Da-Yong; Song, Liang; Guo, Liang-Chen; Bai, Mei; Han, Pei-Jie; Zhu, Hai-Yan; Wen, Zhang (Frontiers in Microbiology, 2026)
Daqu, the core fermentation starter for Chinese Baijiu, harbors intricate and functionally important fungal communities. To comprehensively characterize its biodiversity, we employed an integrated approach combining third-generation amplicon sequencing with culturomics to systematically investigate the fungal communities in low-, medium-, and high-temperature Daqu. Our analysis identified 109 amplicon sequence variants and 135 cultivable isolates, encompassing both cultivable and non-cultivable fungal taxa. Third-generation sequencing revealed greater fungal species richness, whereas culturomics effectively isolated dominant functional fungi, including Saccharomycopsis fibuligera and Lichtheimia ramosa. Moreover, the fungal communities in Daqu exhibited distinct temperature-dependent patterns, with the thermophilic fungus Thermoascus crustaceus being the predominant species in high-temperature Daqu. This integrative approach provides complementary insights into the fungal ecology of Daqu and establishes a foundation for the development fungal resources with potential industrial applications.